New Headway. Elementary: Student's Book - Soars L. Liz (New York, Oxford University Press, 2010)
The THIRD editionNew Headway ElementaryThe world's most trusted English courseNew Headway is the course teachers and learners can rely on. Why? An authoritative integrated syllabus, motivating topics, and clearly focused tasks combine with a real understanding of what works in the classroom. It all makes for effective teaching and effective learning.Tried and tested all over the world, it's probably the most popular course ever written!In the THIRD edition Teacher's Book, full support for the teacher: Crystal-clear lesson plans Integrated answer keys and tapescripts Thorough and informative coverage of grammar points Hints and ideas for preparation and remedial work How to deal with likely problems and common errors 95% new photocopiable materials, Stop and check reviews and Progress Tests